The Influence of Helium Dielectric Barrier Discharge Jet (DBDjet) Plasma Treatment on Bathocuproine (BCP) in p-i-n-Structure Perovskite Solar Cells - Chung-Yueh Shih (MDPI AG, 2021)
A bathocuproine (BCP) layer is typically used as the hole-blocking layer in p-i-n-structure perovskite solar cells (PSCs) between PC61BM and Ag electrodes. Before evaporating the Ag, we used a low-temperature (<40 °C) atmospheric-pressure dielectric barrier discharge jet (DBDjet) to treat the BCP with different scan rates. The main purpose of this was to change the contact resistance between the BCP layer and the Ag electrodes through surface modification using a DBDjet. The best power conversion efficiency (PCE) of 13.11% was achieved at a DBDjet scan rate of 2 cm/s. The He DBDjet treatment introduced nitrogen to form C−N bonds and create pits on the BCP layer. This deteriorated the interface between the BCP and the follow-up deposited-Ag top electrode. Compared to the device without the plasma treatment on the BCP layer, the He DBDjet treatment on the BCP layer reduced photocurrent hysteresis but deteriorated the fill factor and the efficiency of the PSCs.